Щодо забезпечення інформаційної безпеки в медичних освітніх закладах України: виклики війни - Маганова, Тамара Валеріївна; Приходченко, С. В.; Дубина, В. О.; Mahanova, T. V.; Prykhodchenko, S. V.; Dubyna, V. O. (My University, 2023)
Активне застосування цифрових технологій та дистанційної форми навчання містить чимало прихованих ризиків, пов’язаних зі сферою безпеки. Російська збройна агресія проти України продемонструвала сучасні загрози, поки що не завжди очевидні та погано вивчені. Мета статті полягає в тому, щоб проаналізувати особливості забезпечення інформаційної безпеки в закладах медичної освіти в Україні в умовах війни та визначити найбільш оптимальних шляхи подолання викликів. У результатах дослідження визначено, що інформаційна безпека освітніх медичних закладів базується на багатофакторній системі, яка забезпечує захист інформаційного навчального простору, запобігає пошкодженню або крадіжці персональних даних усіх учасників освітнього процесу та інформації, що має наукову, навчальну, фінансову цінність, сприяючи водночас безперебійному функціонуванню установи. Так само встановлено, що в умовах воєнного стану атаки хакерських груп є актуальною небезпекою, що потребує відкритої реакції. Визначено, що існує чотири груп об’єктів, особливо вразливих щодо шкідливого впливу: спеціальна комп’ютерна техніка, спеціальні симулятивні та цифрові інструменти, інформація освітніх медичних закладів, учасники освітнього процесу та їх свідомість. The active use of digital technologies and distance education contains many hidden risks related to security. Russia's armed aggression against Ukraine has demonstrated modern threats that are in service, but not always obvious, as they are still poorly studied and their use is not advertised. The purpose of the article is to analyze the features of ensuring information security in medical education institutions in Ukraine against the background of overcoming and studying the main challenges of the war and determining the most optimal ways to overcome them. The results of the study determined that the information security of educational medical institutions is based on a multifactorial system that ensures the protection of the information learning space, prevents damage or theft of personal data of all participants in the educational process and information that has scientific, educational, financial and other values, while contributing uninterrupted functioning of the institution. It was also investigated that in the conditions of martial law attacks by hacker groups are an actual danger that requires an open response. It was determined that there are five groups of objects that are vulnerable to harmful effects: special computer equipment, special simulation and digital tools, information of educational medical institutions, participants of the educational process and their consciousness.
Regarding the provision of information security in medical educational institutions of Ukraine: the challenges of war
Маганова Т. В. - https://orcid.org/0000-0001-7008-3102
Keywords: російсько-українська війна; медична освіта; безпека; кібер-атаки; дистанційна освіта; Russian-Ukrainian war; medical education; security; cyber attacks; distance education